The Effectiveness of Socio-Demographical Effects on Least Subsistence and Estimating Poverty Line of Iran Urban Areas by Using Panel ELES - Afghah, Morteza; Arman, Aziz; Mansouri, Amin (Asian Journal of Empirical Research, 2014)
In this Paper, the poverty line has been determined through the extended linear expenditure system using the 2S-GMM during 1982-2007 panel data in Iran urban areas. In this way, four factors of employed members of a family, kind of family possession, the literacy level of family head, and the family size on the least subsistence were examined. The results show that family size has a positive relationship with all of the commodity groups’ least subsistence while the rate of family employees has a positive relationship with commodity groups this relationship is negative only for the food group. The most important feature about the estimation results is the increasing trend of poverty line and changes in least subsistence. According to these results, the monthly poverty line for Iran urban areas has increased from 171 in 1982 to 477 in 2007. That is, the poverty line has increased 2.8 times during the study period. The result of this study shows that during this study the food and dwelling share have given their place to the transportation and other services share, i.e. the priority of meeting basic needs, food and dwelling, is given to other needs, while the social affairs’ share has been remained fixed.